Allantoin Inhibits Compound 48/80-Induced Pseudoallergic Reactions In Vitro and In Vivo - Zhang, Ping; Wang, Yanjie; Zhang, Jingyu; Hong, Tie (Molecules (Basel, Switzerland), 2022)
Pseudoallergic reactions are hypersensitivity reactions mediated by an IgE-independent mechanism. Since allantoin (AT)-mediated pseudoallergy has not been studied, in this study, our objective is to investigate the anti-pseudoallergy effect of AT and its underlying mechanism. In vitro, β-hexosaminidase (β-Hex) and histamine (HIS) release assays, inflammatory cytokine assays, toluidine blue staining, and F-actin microfilament staining were used to evaluate the inhibitory effect of AT in RBL-2H3 cells stimulated with Compound 48/80 (C48/80). Western blot analysis is further performed to investigate intracellular calcium fluctuation-related signaling pathways. In vivo, Evans Blue extraction, paw swelling, and the diameter of Evans Blue extravasation were evaluated, and skin tissues are examined for histopathological examination in mice with passive cutaneous anaphylaxis (PCA) induced by C48/80. Body temperature is measured, and the levels of cytokines are further determined by ELISA kits in mice with active systemic anaphylaxis (ASA) induced by C48/80. The results show that AT dose-dependently inhibited degranulation in C48/80-stimulated RBL-2H3 cells by inhibiting β-Hex and HIS release, reducing the levels of TNF-α, IL-8, and MCP-1, inhibiting shape changes due to degranulation and disassembling the F-actin cytoskeleton. Furthermore, AT dose-dependently inhibits the phosphorylation of PLCγ and IP3R. In vivo, AT decreased Evans Blue extravasation, paw swelling, and the diameter of Evans Blue extravasation and significantly ameliorate pathological changes and mast cell degranulation in C48/80-induced PCA. Furthermore, AT help the mice recover from the C48/80-induced decrease in body temperature and decreased the levels of cytokines in C48/80-treated ASA mice. Our results indicate that allantoin inhibits compound 48/80-induced pseudoallergic reactions. AT has the potential to be used in IgE-independent anti-allergic and anti-inflammatory therapies.